Ccr4 Alters Cell Size in Yeast by Modulating the Timing of CLN1 and CLN2 Expression - Manukyan, Arkadi (Genetics Society of America, 2008)
Large, multisubunit Ccr4-Not complexes are evolutionarily conserved global regulators of gene expression. Deletion of CCR4 or several components of Ccr4-Not complexes results in abnormally large cells. Since yeast must attain a critical cell size at Start to commit to division, the large size of ccr4Δ cells implies that they may have a size-specific proliferation defect. Overexpression of CLN1, CLN2, CLN3, and SWI4 reduces the size of ccr4Δ cells, suggesting that ccr4Δ cells have a G(1)-phase cyclin deficiency. In support of this, we find that CLN1 and CLN2 expression and budding are delayed in ccr4Δ cells. Moreover, overexpression of CCR4 advances the timing of CLN1 expression, promotes premature budding, and reduces cell size. Genetic analyses suggest that Ccr4 functions independently of Cln3 and downstream of Bck2. Thus, like cln3Δbck2Δ double deletions, cln3Δccr4Δ cells are also inviable. However, deletion of Whi5, a transcriptional repressor of CLN1 and CLN2, restores viability. We find that Ccr4 negatively regulates the half-life of WHI5 mRNAs, and we conclude that, by modulating the stability of WHI5 mRNAs, Ccr4 influences the size-dependent timing of G(1)-phase cyclin transcription.